Exploring Student Teachers’ Current Digital Competencies for Navigating Digital Education - Regina Putri Nernere; Aprilia Dyah Kriswinahyu; Barli Bram (Universitas Muhammadiyah Tangerang, 2025)
Along with the digital era enhancement, the criteria for qualified teachers to possess not only content and pedagogical knowledge but also technological competence. This study examined the digital competencies of 47 fifth-semester English education students at Sanata Dharma University. Grounded in the TPACK framework, this study explored student teachersâ€™ competencies to integrate technology into English language teaching. This study used a mixed-methods approach. The qualitative data showed that student teachers demonstrated an average digital competency score of 76.87 (SD = 9.73). Qualitative findings revealed that student teachers' digital competencies are shown through innovative teaching practices, information literacy and evaluation, collaboration and resource sharing, responsible technology use, and technical know-how. The study's insights are expected to inform curriculum makers, educators, and policymakers about the current state of digital competencies among future English student teachers, allowing more targeted improvements in teacher education programs.Â